2014
DOI: 10.1185/03007995.2014.901941
|View full text |Cite
|
Sign up to set email alerts
|

US practitioner prescribing practices and patient characteristics of those newly treated with a buprenorphine transdermal patch system

Abstract: Objectives: Medication prescribing information provides guidance to healthcare providers on how to prescribe a drug properly. Oftentimes patient factors in addition to the prescribing information are considered when selecting medications. Utilizing real-world pharmacy and medical claims data, this study assessed US practitioner prescribing practices of US approved transdermal buprenorphine system (BTDS) in relation to BTDS's full prescribing information (FPI) as well as the relationship between patient factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…A weakness of the database is that it cannot link individual patient characteristics to the risk of abuse or suicide, and therefore cannot control for demographic or dose covariates. The majority of people dispensed the buprenorphine patch use it concomitantly with other opioid analgesics [59], so that the overall prescribed daily opioid dose of patients prescribed buprenorphine patch is similar to that of other extended-release opioids (unpublished IMS data). However future studies may wish to use additional databases to control for patient-level differences, although such database studies will probably be limited to abuse and suicide among patients prescribed opioids rather than the substantial proportion who misused diverted opioids obtained from friends, family or black market dealers [60].…”
Section: Resultsmentioning
confidence: 99%
“…A weakness of the database is that it cannot link individual patient characteristics to the risk of abuse or suicide, and therefore cannot control for demographic or dose covariates. The majority of people dispensed the buprenorphine patch use it concomitantly with other opioid analgesics [59], so that the overall prescribed daily opioid dose of patients prescribed buprenorphine patch is similar to that of other extended-release opioids (unpublished IMS data). However future studies may wish to use additional databases to control for patient-level differences, although such database studies will probably be limited to abuse and suicide among patients prescribed opioids rather than the substantial proportion who misused diverted opioids obtained from friends, family or black market dealers [60].…”
Section: Resultsmentioning
confidence: 99%
“…In our aged care residents, 45% of patients prescribed a buprenorphine patch were opioid‐tolerant prior to initiation. A US study found that 92% of patients commencing buprenorphine were opioid‐tolerant, 18 while a German postmarketing surveillance study found that 70% of new users were opioid‐tolerant 19 . However, these studies were not conducted in residential aged care settings.…”
Section: Discussionmentioning
confidence: 99%